PENERAPAN SANGASKARA DANDA DI DESA PAKRAMAN DARMASABA, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - I Putu Sarjana (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2018)
The Government of Bali focus on accelerating development to improve peoples welfare. Regional economic development is an activity where local governments and communities manage existing resources and form partnerships between local governments and the private sector to create new jobs and stimulate the development of economic activities within the region, in support of economic business need to pay attention to the values ethics consistent with religious teachings. The inhabitants of Bali including its entrepreneurs are supporters of a culture that is imbued with religion. As a supporter of culture, their role is crucial in the growth and development of religious life, culture and the activity of economic development. The main pattern of Balinese development establishes the culture that complete the Hindu spirit as the basic capital of regional development. There are two interrelated things between business economics and ethics, business can not be separated by the social culture where ethics is implemented. A business activity must be carried out with the ethical values prevailing in the business community.